Protein Uncoupling as an Innovative Practice in Diabetes Mellitus Treatment: A Metabolic Disorder - Chaudhary, Rishabh; Gupta, Sumeet; Chauhan, Samrat (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Uncoupling proteins (UCPs) are unpaired electron carriers that uncouple oxygen intake by the electron transport chain from ATP production in the inner membrane of the mitochondria. The physiological activities of UCPs have been hotly contested, and the involvement of UCPs in the pathogenesis and progression of diabetes mellitus is among the greatest concerns. UCPs are hypothesised to be triggered by superoxide and then reduce mitochondrial free radical production, potentially protecting diabetes mellitus patients who are experiencing oxidative stress. Objectives: The objectives of the study are to find out the newest ways to treat diabetes mellitus through protein uncoupling. Methods: Research and review papers are collected from different databases like google scholar, PubMed, Mendeley, Scopus, Science Open, Directory of open access journals, and Education Resources Information Center, using different keywords such as
Keywords: Uncoupling proteins